2008
DOI: 10.1002/prot.21706
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of inhibitory peptide maurotoxin recognizing Kv1.2 channel explored by ZDOCK and molecular dynamic simulations

Abstract: Inhibitory peptide-channel interactions have been utilized to characterize both channels and peptides; however, the fundamental basis for these interactions remains elusive. Here, combined computation methods were employed to study the specific binding of maurotoxin (MTX) peptide to Kv1.2 channel. In the first stage, numerous predicted complexes were generated by docking an ensemble of all 35 NMR conformations of MTX to Kv1.2 channel with ZDOCK program. Then the resulted complexes were clustered and classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 41 publications
6
88
1
Order By: Relevance
“…1C). To understand this discrepancy, a computational technique was used to determine the structural conformation of the mSlo turret (15,16). For the unbound mSlo channel, the starting structure of mSlo was found to be very unstable during the 5-ns molecular dynamic simulations (MDs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1C). To understand this discrepancy, a computational technique was used to determine the structural conformation of the mSlo turret (15,16). For the unbound mSlo channel, the starting structure of mSlo was found to be very unstable during the 5-ns molecular dynamic simulations (MDs).…”
Section: Resultsmentioning
confidence: 99%
“…The following procedures of clustering and screening of reasonable ChTX-mSlo complex structures were similar to our previous work (15,16).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Several theoretical docking studies have suggested that this lysine residue protrudes into the channel selectivity filter (Yi et al, 2008;Chen et al, 2011;Chen and Chung, 2012), but in this case K16, K17, and R9 were the most active residues, followed by K30, K25, K32, and K4, in forming hydrogen bonds with E355, E353, and D379, and D363 in the turret and pore helix region, respectively (Supplemental Table 1). A hydrogen bond is considered formed if the donor and acceptor atoms (nitrogen or oxygen) are within 3.2 Å of each other.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…This program was employed for identifying the most reasonable candidate complexes. The detailed method of calculating binding free energies between inhibitory peptides and potassium channels was previously described (29,30).…”
Section: Molecular Dynamic Simulations and Calculation Of Binding Freementioning
confidence: 99%